Comparison of training process and competitive activity characteristics in elite biathletes in different seasons - Adodin, N. V.; Myakinchenko, P. E. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to profile the training systems of the national women`s biathlon team (NT) versus its seasonal competitive performance. Conclusion: The study data and analyses showed that a seasonal competitive progress in the elite women`s biathlon may be secured in most of the competitive events and progress factors. It was demonstrated that the sample made progress in the successful season due to the following changes in the training system: reductions in every training element, particularly in the strength training and high-intensity training ones, with no significant variations in the shooting training components.